Socialism, capitalism, and class struggle: the political economy of modern China - Li, Minqi (2008)
This essays traces the evolution of the political economy of China from the 1949 revolution up to the triumph of Chinese capitalism in 1992. It first describes and discusses the tremendous achievements in the first quarter century after the revolution, and also the struggles during the Great Leap Forward and the cultural revolution. The essay outlines the context of the tussles that followed the death of Mao, the role of the "intellectuals", the alliance or the lack of it with the urban working class during Tiananmen 1989 and how the forces represented by Deng Xiapoing were able to impose their writ on the economy and society of china. - Reproduced.
Keywords: Economics - China; Capitalism - China; Socialism - China; Socialism